Rib waveguides based on the sol-gel derived SiO2 :TiO2 films - Karasiński, Paweł; Tyszkiewicz, Cuma; Rogoziński, Roman (Photonics Letters of Poland, 2010)
This work presents rib waveguides fabricated by chemical etching of inorganic two-component SiO2:TiO2 films. Silica-titania films were fabricated using sol-gel method. In all technological processes involving masking, standard photolithographic procedures were used. A photoresist was used as a mask in the chemical etching processes. Rib waveguides of 5 nm rib height and rib width of less than 4μm were single mode for a wavelength of λ=635nm. The attenuation determined for fabricated rib waveguides approximately equal to 1,5dB/cm. Full Text: PDF References: P. Karasiński, R. Rogoziński, "Rib waveguides fabricated by means of chemical etching of sol-gel films SiO2:TiO2", Optics Communications 245, 237-242 (2005).[CrossRef] P. Karasiński, C. Tyszkiewicz, R. Rogoziński, J. Jaglarz, J. Mazur, "Optical rib waveguides based on sol-gel derived silica-titania films", the paper sent to Thin Solid Films. K.S. Chiang, "Effective-index analysis of optical waveguides", Proc. SPIE 2399, 2-12 (1995).[CrossRef] C.J. Brinkner, G.W. Scherer, Sol-gel science, (San Diego, Academic Press, Inc. 1990). P. Karasiński, Opt. Appl. 34, 467 (2007). P. Karasiński, Act. Phys. Pol. A 116, 114 (2009).